Penguatan Kapasitas Kader Posyandu dalam Mitigasi Risiko Kesehatan Keluarga untuk Mendukung Human Security - Apriyanti Widiansyah; Heni Rohaeni; Rahmat Saputra (Abdi Bhara, 2026)
Strengthening the capacity of Posyandu cadres is an important strategy for mitigating family health risks as part of efforts to support human security at the community level. Posyandu cadres play a strategic role as the frontline providers of basic healthcare services, functioning in health education, health monitoring, early risk detection, and family assistance in maintaining health and well-being. This Community Service Program aims to analyze the importance of strengthening the capacity of Posyandu cadres in enhancing their ability to mitigate family health risks in order to support the creation of sustainable human security. The method employed is a literature review, examining various scientific sources related to health cadre empowerment, health risk mitigation, and human security. The findings indicate that improving cadre capacity through training, mentoring, strengthening health literacy, and utilizing information technology can enhance their competence in identifying health risk factors, conducting preventive health education, and strengthening family resilience against various health threats. Furthermore, the active involvement of Posyandu cadres contributes to improving access to healthcare services, reducing disease risks, enhancing nutritional status, and strengthening community preparedness in facing public health emergencies. Strengthening the capacity of Posyandu cadres also supports the achievement of the Sustainable Development Goals (SDGs), particularly in the areas of health and community well-being. Therefore, continuous support from the government, healthcare professionals, educational institutions, and the community is needed to optimize the role of Posyandu cadres as agents of change in realizing healthy, resilient, and secure families as the primary foundation of human security